HUBUNGAN PENGETAHUAN REMAJA PUTRI TENTANG POLA MAKAN SEHAT DENGAN KENAIKAN BERAT BADAN - Nelfi Sarlis; Susi Hartati; Yesi Arisonaidah (Ensiklopedia of Journal, 2022)
During menstruation, some young women will experience menstrual pain (dysmenorrhea). The results of a recent study show that almost 10% of adolescents with dysmenorrhea experience school absences and work absences 1-3 days per month. One of the efforts to overcome menstrual pain is by non-pharmacological therapy using red ginger decoction. This study aims to determine the effectiveness of giving Red Ginger to the intensity of menstrual pain in adolescent girls at SMP IT Insan Utama Pekanbaru in 2022. The type of research used is quantitative, namely Quasi Experiment with pre and post test design. The research time is from March - May 2022 at SMP IT Insan Utama Pekanbaru. The population is 30 people using consecutive sampling technique, obtained a sample of 14 people. Data analysis used univariate and bivariate analysis. Univariate results from 14 respondents who were given red ginger stew there was a decrease in menstrual pain before being given red ginger stew the majority experienced mild pain and severe pain each amounting to 5 people (36%) and a decrease after being given red ginger stew the majority of respondents experienced mild pain, namely 7 people (50%). The results of the Wilcoxon obtained a p value <  0.001 < 0.05 then Ho is rejected Ha is accepted, meaning that there is an effectiveness of red ginger stew on reducing menstrual pain in adolescents at SMP IT Insan Utama Pekanbaru in 2022. It is recommended to SMP IT Insan Utama Pekanbaru students to be able to consume red ginger stew as an alternative to reduce menstrual pain.